Evaluation of hazelnut kernel oil of Turkish origin as alternative fuel in diesel engines - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
In the present study, hazelnut kernel oil of Turkish origin was evaluated as alternative fuel in a diesel engine. Potential hazelnut production throughout the world and the status of Turkey were examined. Hazelnut (Corylus avellana L.) kernel oil was transesterified with methanol using potassium hydroxide as catalyst to obtain hazelnut kernel oil methyl ester (HOME) and a comprehensive experimental investigation was carried out to examine performance and emissions of a direct injection diesel engine running with HOME and its blends with diesel fuel. Experimental parameters included the percentage of HOME in the blend, engine load, injection timing, compression ratio, and injector. The cost analysis of HOME production comparing to the price of conventional diesel fuel was performed for last decade was performed. Results showed that HOME and its blends with diesel fuel are generally comparable to diesel fuel and small modifications such as increasing injection timing, compression ratio and injector opening pressure provide significant improvement in performance and emissions. It is also expected that the price of HOME will be lower than the price of conventional diesel fuel in the near future. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: biodiesel; hazelnut kernel oil; methyl ester; blends; performance; emissions; METHYL-ESTER; VEGETABLE-OIL; PERFORMANCE; BLENDS; COMBUSTION; VARIETIES